Litter dominates surface fluxes of carbonyl sulfide in a Californian oak woodland. Issue 2 (13th February 2016) - Sun, Wu; Maseyk, Kadmiel; Lett, Céline; Seibt, Ulli
Abstract: Carbonyl sulfide (COS) is a promising tracer for partitioning terrestrial photosynthesis and respiration from net carbon fluxes, based on its daytime co‐uptake alongside CO2 through leaf stomata. Because ecosystem COS fluxes are the sum of plant and soil fluxes, using COS as a photosynthesis tracer requires accurate knowledge of soil COS fluxes. At an oak woodland in Southern California, we monitored below‐canopy surface (soil + litter) COS and CO2 fluxes for 40 days using chambers and laser spectroscopy. We also measured litter fluxes separately and used a depth‐resolved diffusion‐reaction model to quantify the role of litter uptake in surface COS fluxes. Soil and litter were primarily COS sinks, and mean surface COS uptake was small (∼1 pmol m −2  s −1 ). After rainfall, uptake rates were higher (6–8 pmol m −2  s −1 ), and litter contributed a significant fraction (up to 90%) to surface fluxes. We observed rapid concurrent increases in COS uptake and CO2 efflux following the onset of rain. The patterns were similar to the Birch effect widely documented for soils; however, both COS and CO2 flux increases originated mainly in the litter. The synchronous COS‐CO2 litter Birch effect indicates that it results from a rapid increase in litter microbial activity after rainfall. We expect that the drying‐rewetting cycles typical for mediterranean and other semiarid ecosystems create a pronounced seasonality in surface COS fluxes. Our results highlight that litter uptake is an important component of surface COS exchange that needs to be taken into account in ecosystem COS budgets and model simulations. Key Points: Leaf litter is a significant COS sink in a mediterranean oak woodland Drying‐rewetting cycles produce bursts in litter COS and CO2 fluxes Litter COS uptake reduces the amount of COS available for soil uptake